Examining the Effectiveness of a Mindfulness-Based Training Program on Achievement Motivation, Self-Confidence, and Sports Performance among Novice Football Students in Iraqi Schools - Mashhoot, Husam Abbas; Faraeen, Maryam; Hoossein Algnabe , Akram; Abdi, Hassan; Meshkati, Zohreh (International Journal of Sport Studies for Health, 2025)
Objective: The purpose of the present study was to examine the impact of a mindfulness-based training program on achievement motivation, self-confidence, and sports performance (shooting, passing, dribbling) among novice football students in Iraqi schools. Materials and Methods: The research participants were 60 male football players, aged 14 to 16, from the city of Baghdad in 2023–2024, selected through a call for participation and randomly assigned to either a mindfulness training group or a control group. Data were collected using Hermans’s (1970) Achievement Motivation Questionnaire, the Moore-Christine tests for dribbling, passing, and shooting skills, and Willy and Knight’s (2002) Sports Self-Confidence Questionnaire. The Shapiro-Wilk test was used to check the normal distribution of the data, and Levene’s test was used to assess the homogeneity of variances. To analyze the findings, analysis of covariance (ANCOVA) was performed using SPSS statistical software, version 24. Findings: The results indicated that scores for self-confidence and the skills of shooting, passing, dribbling, as well as achievement motivation, improved in the experimental group compared to the control group. In other words, mindfulness training had a positive and significant effect on self-confidence, shooting, passing, dribbling, and achievement motivation among novice football students in Iraq. Conclusion: Based on the findings, it can be concluded that mindfulness training plays a crucial role in enhancing skill levels, achievement motivation, and sports self-confidence in Iraqi football novices; therefore, it is recommended that coaches employ mindfulness training to improve performance and increase sports self-confidence and achievement motivation.